PROBLEM SOSIAL DAN BUDAYA - Wiryokusumo, Iskandar (Jurnal Budaya Nusantara, 2018)
Social problems in society often occur in increasingly complex social environments. Many things happen which are in line with human life that continues to evolve and fluctuate especially it happens in developing countries. This is usually caused by the existence of social sustainability in a community group and arousing social jealousy, thus generate to behavior with certain characteristics. Through several theories, the behavior is reviewed and the symptoms are also observed. Finally, a simple understanding is obtained, that social problems are caused by, among others; 1) young generation movements, 2) poverty groups, 3) education groups. It is not the wrong educational process, but the supporting factors that are not in line with the values in the learning process are the factors that support the problem insociety.